INCREASE IN ORAL CAVITY DISEASES AMONG POST-COVID-19 PATIENTS - Baxodurov Botirxon Nodir oʻgʻli (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: The COVID-19 pandemic has affected nearly every aspect of human health, including the oral cavity. Emerging clinical data suggest that individuals recovering from SARS-CoV-2 infection are at increased risk for various oral diseases such as xerostomia, oral candidiasis, ulcerative lesions, gingivitis, and opportunistic infections. This article explores the potential mechanisms linking COVID-19 to oral health deterioration, including immune dysregulation, long-term medication effects, and altered salivary flow. The study also reviews post-COVID trends in oral disease prevalence and outlines methods for effective screening, diagnosis, and dental management of post-viral oral complications.